El Excentrico, 1968-10-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
October 5, 1968 [5 de octubre de 1968]. No volume or issue number. Cover has a photo of Crandall, waving to a crowd, with headline, "Re -Elect Assemblyman Crandall. Performance.... not promises."